The effect of hypoxia and hyperoxia on nucleoside triphosphate/inorganic phosphate, pO2 and radiation response in an experimental tumour model. - Nordsmark, M. (Nature Publishing Group, 1997)
This study has evaluated the effect of breathing 100% oxygen, carbogen and carbon monoxide (at 660 p.p.m.) on the bioenergetic and oxygenation status and the radiation response of 200-mm3 C3H mammary carcinomas grown in the feet of CDF mice. Bioenergetic status was assessed by 31P magnetic resonance spectroscopy (MRS) using a 7-tesla spectrometer with both short (2 s) and long (6 s) pulse repetition times. Tumour partial pressure of oxygen (PO2) was measured with an Eppendorf polarographic electrode; the oxygenation parameters were the median pO2 and fraction of pO2 values < or = 2.5 mmHg. The radiation response was estimated using a tumour growth delay assay (time to grow three times treatment volume). Carbon monoxide breathing decreased tumour pO2 and compromised the radiation response, but the beta-nucleoside triphosphate (NTP)/Pi ratio was unchanged. Both carbogen and oxygen (100%) increased tumour pO2 and beta-NTP/Pi and enhanced the radiation response, the effects being similar under the two gassing conditions and dependent on the gas breathing time. Thus, in this tumour model, 31P-MRS can detect hyperoxic changes, but because cells can remain metabolically active even at low oxygen tensions the beta-NTP/Pi did not correlate with low tissue oxygenation. An analysis of variance showed that gas breathing time induced a significant systematic effect on beta-NTP/Pi, the MRS pulse repetition time had a significant effect on beta-NTP/Pi change under hypoxic but not under hyperoxic conditions and the type of gas that was inhaled had a significant effect on beta-NTP/Pi. IMAGES: